2013
DOI: 10.1007/s00253-013-5164-7
|View full text |Cite
|
Sign up to set email alerts
|

Importance of codB for new codA-based markerless gene deletion in Gluconobacter strains

Abstract: For the detailed molecular analysis, genomic modification, and application of acetic acid bacteria such as Gluconobacter in biotechnological processes, a simple markerless deletion system is essential. The available methods have either low efficiencies or their applicability is restricted to strains containing an upp mutation. We now developed a method based on counterselection by cytosine deaminase, encoded by the codA gene from Escherichia coli, in the presence of the fluorinated pyrimidine analogue 5-fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…Positive clones were selected by colony PCR and the correct insertion of the PCR products was checked by sequencing (StarSEQ GmbH, Mainz, Germany). For the generation of G. oxydans strains carrying in-frame deletion mutations for gox1432 and/or gox0849, the codAB markerless in-frame deletion system was used (Kostner et al 2013). For the generation of the Δgox1432 mutant 1 kb of the up-and downstream regions were amplified using primers up_ gox1432_Fw/up_gox1432_Rev and do_gox1432_Fw/do _gox1432_Rev (Table 1).…”
Section: Standard Molecular Biology Techniques and Cloningmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive clones were selected by colony PCR and the correct insertion of the PCR products was checked by sequencing (StarSEQ GmbH, Mainz, Germany). For the generation of G. oxydans strains carrying in-frame deletion mutations for gox1432 and/or gox0849, the codAB markerless in-frame deletion system was used (Kostner et al 2013). For the generation of the Δgox1432 mutant 1 kb of the up-and downstream regions were amplified using primers up_ gox1432_Fw/up_gox1432_Rev and do_gox1432_Fw/do _gox1432_Rev (Table 1).…”
Section: Standard Molecular Biology Techniques and Cloningmentioning
confidence: 99%
“…Finally, pKos6bΔ1432 was transferred from E. coli NEB 5-α into G. oxydans with the help of E. coli ECG 18 by triparental mating (Condon et al 1991). The markerless deletion of gox1432 was generated by plating G. oxydans pKos6 bΔ1432 on 5-fluorocytosine containing agar plates as described by Kostner et al (2013). The construction of the Δgox0849 mutant and the double mutant (Δgox1432 Δgox0849) was performed analogously.…”
Section: Standard Molecular Biology Techniques and Cloningmentioning
confidence: 99%
“…In developing a markerless gene deletion system for acetic acid bacteria, Kostner et al . () found that introducing the E. coli cytosine permease gene codB alongside codA decreased the minimum inhibitory concentration of 5‐FC eightfold due to increased uptake of 5‐FC. Another approach involves co‐expression of a uracil phosphoribosyltransferase enzyme with codA to increase conversion of 5‐FU to 5‐fluorouridine 5′‐monophosphate, enhancing the cytotoxicity of 5‐FC (Tiraby et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several homology-directed repair (HDR)-based genetic modification technologies have been developed in the model microorganism, Escherichia coli , and two-step strategies including a negative selection step make it possible to perform markerless genome editing (Datsenko and Wanner, 2000; Tischer et al, 2006; Peters et al, 2013; Wang et al, 2014). A large number of toxic genes have been verified to work well as negative selection markers in E. coli , including sacB, ccdB and codAB (Yu et al, 2008; Kostner et al, 2013; Wang et al, 2014). However, the efficiency is low during the second step of crossover to lose the toxic genes.…”
Section: Introductionmentioning
confidence: 99%